Participation, retention and uptake in a multicentre pre‐exposure prophylaxis cohort using online, smartphone‐compatible data collection. Issue 2 (3rd October 2021) - Hovaguimian, F; Martin, E; Reinacher, M; Rasi, M; Schmidt, AJ; Bernasconi, E; Boffi El Amari, E; Braun, DL; Calmy, A; Darling, K; Christinet, V; Depmeier, C; et al.
Abstract: Objectives: The aim of the study was to assess the feasibility of a national pre‐exposure prophylaxis (PrEP) programme using smartphone‐compatible data collection. Methods: This was a multicentre cohort study (NCT03893188) enrolling individuals interested in PrEP in Switzerland. All centres participate in the SwissPrEPared programme, which uses smartphone‐compatible data collection. Feasibility was assessed after centres had enrolled at least one participant. Participants were HIV‐negative individuals presenting for PrEP counselling. Outcomes were participation (number enrolled/number eligible), enrolment rates (number enrolled per month), retention at first follow‐up (number with first follow‐up/number enrolled), and uptake (proportion attending first visit as scheduled). Participant characteristics were compared between those retained after baseline assessment and those who dropped out. Results: Between April 2019 and January 2020, 987 individuals were assessed for eligibility, of whom 969 were enrolled (participation: 98.2%). The median enrolment rate was 86 per month [interquartile range (IQR) 52–137]. Retention at first follow‐up and uptake were both 80.7% (782/969 and 532/659, respectively). At enrolment, the median age was 40 (IQR 33–47) years, 95% were men who have sex with men, 47% had a university degree, and 75.5% were already taking PrEP. Most reported multiple casual partners (89.2%), previous sexually transmitted infections (74%) and sexualized drug use (73.1%). At baseline, 25.5% tested positive for either syphilis, gonorrhoea or chlamydia. Participants who dropped out were at lower risk of HIV infection than those retained after baseline assessment. Conclusions: In a national PrEP programme using smartphone‐compatible data collection, participation, retention and uptake were high. Participants retained after baseline assessment were at considerable risk of HIV infection. Younger, less educated individuals were underrepresented in the SwissPrEPared cohort.